The impact of mental health, work-life balance, and organizational support on burnout: Perspectives of employees in the creative industry - Sadiqin, Amin; Halik, Abdul; Mujanah , Siti (Keynesia : International Journal of Economy and Business, 2025)
This study aims to analyze and understand the impact of mental health, work-life balance, and organizational support on burnout among employees in the creative industry. The phenomenon of burnout has become an increasingly serious issue among creative workers due to high work pressure, tight deadlines, and demands for continuous innovation. The research approach used is descriptive qualitative, with data collection methods through in-depth interviews with a number of employees from various creative industry sub-sectors, such as graphic design, advertising, and media production. The results show that good mental health plays an important role in reducing burnout levels; individuals with adequate stress management and psychological support tend to have higher emotional resilience. A balanced work-life balance helps employees maintain productivity without losing motivation and personal satisfaction. Meanwhile, organizational support has been shown to be a protective factor that strengthens work engagement and reduces the risk of emotional exhaustion. These findings reinforce the relevance of the model that explains that burnout occurs when work demands are not balanced with the availability of personal and organizational resources. This research confirms that the synergy between mental health, life balance, and organizational support is crucial for preventing burnout and creating a sustainable work environment in the creative industry.